Developing an Islamic Corporate Governance framework to examine sustainability performance in Islamic Banks and Financial Institutions - Jan, A.A. (Elsevier Ltd, 2021)
Academic and industry interest in sustainable development has increased significantly, which is evident from the number of publications in recent years. To develop the field further, this study conceptualizes a framework to establish the nexus of Islamic Corporate Governance (ICG) and Sustainability Performance (SP) in Islamic Banks and Financial Institutions (IBFIs). Although strong corporate governance practices are crucial for maintaining financial stability and development. Nevertheless, scant practical guidance is available on how multidimensional functions of Islamic CG affect the IBFIs' sustainability performance. A conscientious examination of the extant ICG literature facilitates the development of a research framework consisting of several research propositions. This study has derived the most influential Islamic CG mechanisms from the theoretical perspective of Agency Theory, Institutional Theory, and Legitimacy Theory and established their relationship with sustainability performance. Explicitly, this research focuses primarily on the key elements of Islamic corporate governance - namely Shariah board attributes and ownership structure - and aims to examine its impact on economic, social, and environmental SP. This study posits the ordinary least square (OLS) for the anticipated analysis. This study offers a rationale way for future research. In theory, Islamic CG's impact on sustainability performance has been elusive and needs more academic consideration. In this study, a total number of six propositions were developed to provide responsible decision-making opportunities to enhance sustainability performance. The research framework and propositions were developed to address the need for Islamic corporate governance procedures to encourage sustainable banking for maintaining financial stability and sustainable growth. This research is likely to add to the existing developmental plans of the Islamic development bank and other concerned authorities in addressing sustainability-related issues. This study provides policy insights to policymakers, practitioners, and corporate boards of the IBFIs to promote sustainable and cleaner operations through Islamic corporate governance. To the best of the authors' knowledge, this is the first study that extends the current literature by establishing the nexus of Islamic corporate governance and triple bottom line performance in IBFIs. Â© 2021